Sleep complaints in former and current night shift workers: findings from two cross-sectional studies in Austria. (3rd June 2021) - Weitzer, Jakob; Santonja, Isabel; Degenfellner, Jürgen; Yang, Lin; Jordakieva, Galateja; Crevenna, Richard; Seidel, Stefan; Klösch, Gerhard; Schernhammer, Eva; Papantoniou, Kyriaki
ABSTRACT: Sleep impairment is highly prevalent in night shift workers, but evidence on the association of former night shift work (NSW) and its metrics (duration and frequency) in relation to sleep complaints is lacking. We evaluated the association of former and current NSW with chronic insomnia or circadian rhythm sleep disorder in a sample of the general worker (GW) population and in hospital workers (HW) in Austria. Information on sleep, NSW history, sociodemographic, and lifestyle factors was collected through an online cross-sectional survey in a representative sample of GW ( N = 1, 004) and a sample of HW ( N = 799) between 2017 and 2019. Multi-variable adjusted logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for various measures of sleep (including chronic insomnia, daytime sleepiness, sleep duration, napping habits) and doctor-diagnosed chronic insomnia across NSW exposure (never night shift work; ever; ever/former; ever/current) and related metrics (cumulative duration, average frequency), compared to never NSW. Effect modification by chronotype and daytime napping was investigated. Former NSW was associated with higher odds of chronic insomnia in both samples (GW: OR = 2.28, 95% CI = 1.07–4.83; HW: OR = 1.17, 95% CI = 0.60–2.27). Chronic insomnia odds tended to increase among current night shift workers (HW: OR = 1.50, 95% CI = 0.79–2.83), compared to day workers. Higher NSW frequency (shifts/month) was associated with higher chronic insomnia odds in former night shift workers in both samples (GW: ORper shift/month = 1.06, 95% CI = 1.00–1.12; HW: ORper shift/month = 1.12, 95% CI = 1.00–1.25). Former NSW was also associated with increased daytime sleepiness among GW (OR = 2.26, 95% CI 1.28–3.99). Associations were more pronounced among early chronotypes and participants who reported no daytime naps. Our results suggest that NSW is associated with chronic insomnia even in the years after cessation of involvement in working it.